English Teachers’ Perceptions of the Transition from the 2013 Curriculum to the Merdeka Curriculum - Adrianus Eban Lamadoken; Nurteteng; Agus Setiawan (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study explores the perceptions of English teachers regarding the transition from the 2013 Curriculum to the Merdeka Curriculum at SMP Negeri 11 Sorong Regency and SMP Muhammadiyah Sorong Regency. Using a descriptive qualitative design, data were collected through interviews with five English teachers—three from SMP Negeri 11 and two from SMP Muhammadiyah. The interviews included ten questions aimed at understanding teachers’ views on curriculum implementation, their responses to the transition, and the challenges they face. The findings reveal that while the Merdeka Curriculum offers benefits such as flexibility and a focus on holistic student development, it also presents significant challenges. These challenges include inadequate training, limited resources, and difficulties in adopting new technologies. Teachers noted both positive and negative aspects of the transition, such as opportunities for personalized learning but also increased workload and the need for more preparation time. Furthermore, the training received was found to have varying levels of effectiveness, highlighting the need for consistent and comprehensive professional development. This study emphasizes the importance of addressing these challenges to ensure the successful and equitable implementation of the Merdeka Curriculum across Indonesia’s diverse educational landscape. Insights from this research can guide policymakers and educators in enhancing teacher support and curriculum adaptation strategies